Sams teach yourself Unix system administration in 24 hours - Taylor, Dave, 1962-; Safari eBooks (Indianapolis, Ind. : Sams, 2003)
"Covers: Unix/Linux/Solaris/Mac OS X"--P. [4] of cover.
Includes index.
Electronic reproduction.
Keywords: UNIX (Computer file); Operating systems (Computers); Electronic books